Brazilian Academy of Neurology practice guidelines for stroke rehabilitation: part I - Minelli, Cesar (2022)
The Guidelines for Stroke Rehabilitation are the result of a joint effort by the Scientific Department of Neurological Rehabilitation of the Brazilian Academy of Neurology aiming to guide professionals involved in the rehabilitation process to reduce functional disability and increase individual autonomy. Members of the group participated in web discussion forums with predefined themes, followed by videoconference meetings in which issues were discussed, leading to a consensus. These guidelines, divided into two parts, focus on the implications of recent clinical trials, systematic reviews, and meta-analyses in stroke rehabilitation literature. The main objective was to guide physicians, physiotherapists, speech therapists, occupational therapists, nurses, nutritionists, and other professionals involved in post-stroke care. Recommendations and levels of evidence were adapted according to the currently available literature. Part I discusses topics on rehabilitation in the acute phase, as well as prevention and management of frequent conditions and comorbidities after stroke.